Advocating The Freethinking Feminist Project Within The Secularist Movement, Britain 1851-1886 - بن عمارة, حمزة (University of Eloued جامعة الوادي, 2023)
This article proposes that the establishment of the Secularist movement by George Jacob Holyoake aimed to champion the Freethinking feminist project. This latter one included a rational critique of religion and support to fallen women’s liberties. In fact, the Freethinkers who held similar radical views were powerfully attacked by the State and society, and their heritage was on the brink of demise. From 1915 through to 1942, the government charged some leading Freethinkers with blasphemous libel and put them in jail. In addition, the far more progressive views of Owen’s schemes about free love unions were on the whole denied in society. Nevertheless, Holyoake’s new articulation of ‘respectability’ within the Secularist movement had provided a way to a number of Freethinking feminists to promote a combination of anti-religious and far more progressive views on prostitution. The astonishing fact is that Freethinkers gained acceptance in society and were not subject to legal prosecutions. So, it could be inferred that the Secularist movement was fertile ground in which Freethinking feminism was able to thrive.